ORGANIZATIONAL AND SOCIAL AND PEDAGOGICAL PRINCIPLES OF SPORTS TOURISM DEVELOPMENT (Scientific journal of the Fergana State University, 2023)
In this article, the concept of sports tourism, its classification, the differentiation of sports tourism according to its goals, motives and results, as well as the widespread development of sports tourism through international sports competitions in Uzbekistan, the ethics of youth sports tourism, knowledge and views on the goals of sports tourism. Opinions were expressed that the inculcation of skills, the expansion of the worldview, the formation of the motor and spiritual qualities of a person is an important factor in the development of the culture of sports tourism.